2019
DOI: 10.2147/oaem.s212617
|View full text |Cite
|
Sign up to set email alerts
|

<p>Success Of An Expedited Emergency Department Triage Evaluation System For Geriatric Trauma Patients Not Meeting Trauma Activation Criteria</p>

Abstract: BackgroundGeriatric patients are at increased risk of injury following low-energy mechanisms and are less tolerant of injury. Current criteria for trauma team activation (TTA) often miss these injuries. We evaluated a novel triage process for an expedited Emergency Medicine Physician evaluation protocol (T3) for at-risk geriatric sub-populations not meeting trauma team activation (TTA) criteria.MethodsRetrospective review of injured patients (≥65 years) from a Level II Trauma Center with an Injury Severity Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…12 32 42 A recent study demonstrated that a specialised protocol to triage older persons in the ED significantly reduces time to physician assessment, as well as overall ED length of stay. 47 This is further supported in other research that suggests triage processes may not address the special care needs of older persons in the ED. 48 Further investigation into these types of interventions could support changes in practice guidelines and the development of new quality measures, such as a structural measure for the presence of a geriatric triage protocol.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…12 32 42 A recent study demonstrated that a specialised protocol to triage older persons in the ED significantly reduces time to physician assessment, as well as overall ED length of stay. 47 This is further supported in other research that suggests triage processes may not address the special care needs of older persons in the ED. 48 Further investigation into these types of interventions could support changes in practice guidelines and the development of new quality measures, such as a structural measure for the presence of a geriatric triage protocol.…”
Section: Discussionmentioning
confidence: 65%
“…Issues meeting timeliness scores may point to larger systemic issues related to availability of ambulances, staff, ED beds or issues of ageism 12 32 42. A recent study demonstrated that a specialised protocol to triage older persons in the ED significantly reduces time to physician assessment, as well as overall ED length of stay 47. This is further supported in other research that suggests triage processes may not address the special care needs of older persons in the ED 48.…”
Section: Discussionmentioning
confidence: 93%
“…Patient outcomes including mortality and morbidity were measured and system performance indicators such as the number of patients included in trauma activation, time to be seen, time to treatment, LOS and patient disposition, were collected. Widening capture of older patients increased existing trauma team workload, but did not always result in better outcomes [ 99 , 102 , 104 ], whereas introduction of a third-tier trauma protocol reduced ED LOS (5.5 h pre vs 4.5 h post; p < 0.01), decreased hospital admissions (98.4% pre vs 61.9% post), and lowered complication rates (16.4% pre vs 1.6% post; p < 0.01) in one study [ 100 ]. However, hospital LOS increased (4.4 days pre vs 4.8 days post; p = 0.02), as did mortality (1.6% pre vs 4.8% post).…”
Section: Resultsmentioning
confidence: 99%
“…Efforts have been made elsewhere to address patients > 65 years of age with low--energy falls, with expedited teams specifically addressed for this group. One study found to decrease length of stay, but with no improvement in mortality after implementing an expedited team [ 17 ]. If we are to provide a decent and optimal care for older patients with low injury falls, a change in the trauma system may be necessary.…”
Section: Discussionmentioning
confidence: 99%